Economic Insights into Tourist Behavior: The Mediating Role of Satisfaction Between Destination Image, Perceived Value, and Revisit Intention in Toronipa Beach - Deniswara, Frederik Pradana; Churiyah, Madziatul; Dhewi, Titis Shinta (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to determine and analyse whether there is an effect of perceived value and destination image on revisit intention with tourist satisfaction as an intervening variable (study on Toronipa beach attractions). This research is quantitative research with descriptive and explanatory research methods. The population in this study were visitors to Toronipa Beach and the sample obtained was 222 people. The data collection technique in this study was to use an online questionnaire. The data analysis technique uses associative and quantitative approaches with SmartPLS software. The results of this study indicate that perceived value has a positive and insignificant effect on revisit intention in Toronipa Beach visitors. Destination image and tourist satisfaction has a positive and significant effect on revisit intention for Toronipa Beach visitors. Perceived value and destination image has a positive and significant effect on tourist satisfaction for Toronipa Beach visitors. Perceived value and destination image indirectly through tourist satisfaction as an intervening variable has a positive and significant effect on revisit intention for Toronipa Beach visitors. Overall to provide theorical developments and practicasl strategies, this study aims to develop a framework that explains tourists’ revisit intention by expanding the Theory of Planned Behavior (TPB).